2019
DOI: 10.1039/c9ta01973a
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the pseudocapacitance of nitrogen-rich carbon nanorod arrays for electrochemical capacitors

Abstract: The ultrahigh N content (∼24%) induced by the low-temperature treatment boosts the pseudocapacitance for carbonaceous materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…[65][66][67] For example, N-rich carbon nanorods prepared by pyrolysis of polyaniline (PANI) nanorod arrays and ammonium sulfate have exhibited specific capacitance of 776 F g −1 at 1 A g −1 with 94.4% retention at 40 A g −1 after 5000 charge-discharge cycles versus reference electrode whereas PANI nanorod arrays showed the capacitance of 408.36 F g −1 at 1 A g −1 with 49.19% retention after 500 cycles. [68] In addition, heteroatom doped nanocarbons have several key features over pseudocapacitive materials while they are utilized as a supercapacitor electrode as follows:…”
Section: The Limited Density Of States At the Fermi Level (Dos(e F ))mentioning
confidence: 99%
See 2 more Smart Citations
“…[65][66][67] For example, N-rich carbon nanorods prepared by pyrolysis of polyaniline (PANI) nanorod arrays and ammonium sulfate have exhibited specific capacitance of 776 F g −1 at 1 A g −1 with 94.4% retention at 40 A g −1 after 5000 charge-discharge cycles versus reference electrode whereas PANI nanorod arrays showed the capacitance of 408.36 F g −1 at 1 A g −1 with 49.19% retention after 500 cycles. [68] In addition, heteroatom doped nanocarbons have several key features over pseudocapacitive materials while they are utilized as a supercapacitor electrode as follows:…”
Section: The Limited Density Of States At the Fermi Level (Dos(e F ))mentioning
confidence: 99%
“…An enhancement in the specific capacitance of the electrode is found to have a linear relationship with N-content up to 7 wt% in 1 m aqueous H 2 SO 4 electrolyte and diluted tetraethylammonium tetrafluoroborate (TEABF 4 ) in propylenecarbonate (PC). [126] Significant efforts have been undertaken to increase the N-content by 29.82 at% in graphitic materials by fluorination (with XeF 2 in Teflon container at 200 °C for 30 h in Ar) followed by the annealing treatment, [37] 45% N/C doped carbons derived from melamine, [127] 21.86 at% in nitrogenrich carbon nanorod arrays by low-temperature pyrolysis using PANI nanorod arrays and ammonium sulfate, [68] and some other methods. It is important to note that the specific capacitance of N-doped nanocarbons is limited to 128.2 F g −1 with 45% N/C, [127] 390 F g −1 at 5 A g −1 with 29.82 at% N 2 , [37] and 203.8 F g −1 at 0.1 A g −1 with 9.7 at% N 2 .…”
Section: Effect Of Nitrogen Content and Atomic Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al and Arrigo et al [26,27] experimentally demonstrated that the Ocontaining functional groups in the precursors could react with some N-containing substance to form CÀ N bond. Yang et al [28] further research indicated that these reactions could occur at 300~500°C. Inspired by these points, utilizing the feature of high O content of biomass-based activated carbon materials, the capacitance can be further improved by introducing of N elements to the surface of activated biomass-based carbon materials.…”
Section: Introductionmentioning
confidence: 98%
“…experimentally demonstrated that the O‐containing functional groups in the precursors could react with some N‐containing substance to form C−N bond. Yang et al . further research indicated that these reactions could occur at 300∼500 °C.…”
Section: Introductionmentioning
confidence: 99%